2016
DOI: 10.1590/1676-0611-bn-2016-0224
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyofauna of the upper Juruena river on Chapada dos Parecis, Mato Grosso, Brazil

Abstract: The fishes herein included were collected in four small streams of the upper rio Tapajós basin. Through fieldwork carried out in 2011, 2013 and 2014 during the low water season 1.728 specimens belonging to 22 species distributed in 11 families, and five orders were captured. Characidae was the most representative family both in number of species and specimens captured. The most abundant species were Hyphessobrycon melanostichos, H. hexastichos, and H. notidanos. Five species are recognized as new, and four as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
4
8
0
2
Order By: Relevance
“…Our results agree with other ichthyofaunistic studies in the upper rio Paraná and other Neotropical rivers, which also found a high diversity of these two orders (e.g. Castro et al 2004;Langeani et al 2007;Vari et al 2009;Esguícero and Arcifa 2011;Ohara and Loeb 2016). Indeed, Siluriformes and Characiformes are the most diverse groups of Neotropical freshwater fishes, followed by Gymnotiformes (Lowe-McConnell 1999;Fricke et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Our results agree with other ichthyofaunistic studies in the upper rio Paraná and other Neotropical rivers, which also found a high diversity of these two orders (e.g. Castro et al 2004;Langeani et al 2007;Vari et al 2009;Esguícero and Arcifa 2011;Ohara and Loeb 2016). Indeed, Siluriformes and Characiformes are the most diverse groups of Neotropical freshwater fishes, followed by Gymnotiformes (Lowe-McConnell 1999;Fricke et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Rarity is another pattern observed from these assemblages since 15% of the species were singletons and 30% were uniques. This high occurrence of rare species mirrors another pattern for Amazonian streams, as indicated by several studies (e.g., Barros et al 2011, Casatti et al 2013, Ohara & Loeb 2016. However, the set of rare species was not the same in Aripuanã River and in Juruena River.…”
Section: Discussionsupporting
confidence: 77%
“…rondoni (Miranda Ribeiro), Erythrinus erythrinus (Bloch & Schneider), Hemigrammus skolioplatus Bertaco & Carvalho, Hyphessobrycon hexastichos Bertaco & Carvalho, H . melanostichos Carvalho & Bertaco, Hasemania nambiquara Bertaco & Malabarba, and Hoplerythrinus unitaeniatus (Spix & Agassiz) (for other species see [46]). No other Gymnotiformes were collected with E .…”
Section: Etymologymentioning
confidence: 99%